Wiley Encyclopedia of Electrical and Electronics Engineering 2014
DOI: 10.1002/047134608x.w3226.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor‐insulator Interfaces, High κ Dielectrics on (In)GaAs

Abstract: Recent development of high κ dielectric oxides on (In) GaAs is reviewed in the fields of electronic structure and electric performance; this includes studies of (In) GaAs surfaces with various surface reconstructions, different orientations, and Indium contents, and of high κ/(In) GaAs interfaces. The oxide deposition was carried out using atomic‐layer deposition ( ALD ) and molecular beam epitaxy ( MBE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…In figure 3(a) of the 2 × 4 surface, the component with the greatest binding energy is the emission from the As-As dimers, which is commonly observed in the literature. See the references listed in [16] and [21]. A sharp LEED image suggests that the As-As dimers here are oriented in a fashion with the long-range order.…”
Section: On Gaas(111)a-2 ×mentioning
confidence: 89%
See 2 more Smart Citations
“…In figure 3(a) of the 2 × 4 surface, the component with the greatest binding energy is the emission from the As-As dimers, which is commonly observed in the literature. See the references listed in [16] and [21]. A sharp LEED image suggests that the As-As dimers here are oriented in a fashion with the long-range order.…”
Section: On Gaas(111)a-2 ×mentioning
confidence: 89%
“…In literature, both in situ [17,20] and ex situ [3,4,6,8] studies of high-κ oxides on (In)GaAs were reported. The former means that a dielectric oxide is deposited on an asgrown (In)GaAs surface, which does not momentarily expose the sample to air whatsoever in either the heterostructure preparation or the measurements of the electronic characteristics [21]. In contrast, an air-exposed (In)GaAs sample is regarded as an ex situ surface, which requires chemical treatments or, if the As is capped, annealing off the capped As in order to obtain a 'clean' surface prior to oxide deposition [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After decades of research, , the first GaAs Fermi-level unpinning was realized by using electron beam (e-beam) evaporated Ga 2 O 3 (Gd 2 O 3 ). , Rare-earth (RE) oxides or mixed oxides containing RE elements have effectively passivated numerous semiconductor surfaces in the past decades, from III−V compound semiconductors of GaAs, , InGaAs, , GaSb, and GaN , to group IVs of Ge , and Si , with low D it values. We have used direct e-beam evaporation of Y 2 O 3 in a molecular beam epitaxy (MBE) type (physical vapor deposition) and atomic layer deposition (ALD) (chemical vapor deposition) to effectively passivate the GaAs surface in achieving D it values below 10 12 eV –1 cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…After decades of research, 5,6 the first GaAs Fermi-level unpinning was realized by using electron beam (e-beam) evaporated Ga 2 O 3 (Gd 2 O 3 ). 7,8 Rare-earth (RE) oxides or mixed oxides containing RE elements have effectively passivated numerous semiconductor surfaces in the past decades, from III−V compound semiconductors of GaAs, 9,10 This article is licensed under CC-BY-NC-ND 4 InGaAs, 11,12 GaSb, 13 and GaN 14,15 to group IVs of Ge 16,17 and Si 18,19 with low D it values.…”
Section: ■ Introductionmentioning
confidence: 99%